DANCES IN CIRCLE: DIFFERENCES AND SIMILARITIES AMONG POPULAR DANCES IN CIRCLE OF BRAZIL (Fiep Bulletin - online, 2014)
The objectives of this study are to understand the popular dances in circle as a manifestation of leisure in the corporal and entertaining culture of the city of Tarituba and to describe the similarities and differences among the practices of popular dances in circle, taking as references those danced in other Brazilian cities. In children entertaining universe of the current society, dances in circle, sung games, free and spontaneous play are restrict to areas inside closed condominiums, and atrophic of action, of movement and of life. Nowadays these manifestations appear in schools where a professional dedicates himself to ransom the value of such activities, promoting popular dances, games and plays in commemorative dates such as the folklore day, for example, and where this same professional notices the possibility of integrating his pupils in a world of creativeness and imagination, or when he accomplishes works in communities which fight for the preservation and maintenance of their cultural traditions and their identities, through dances, parties, stories, beliefs, plays and popular games, as the people of the community of fishermen of Tarituba do. The popular dances in circle have a symbology which assumes a role in the building of situations which favour and help the process of teaching and learning in schools and in the cultural development of certain communities. The circle symbolizes power, totality; it has neither beginning nor end. The wheel spinning round is a symbol of time, of infinite time. When dancers dance in circle it's like they are around the center of the universe. The tradition, the fantasy, the entertaining and the imaginary identify these circle dancers-fishermen-players. So, the individuals of a society assimilate the sense of that which is close to their needs and wishes giving them meaning, which to be studied and understood needs to be inferred taking into consideration the ideas of general culture in which it is inserted.
Keywords: leisure; Social imaginary; Clture of games; plays